emberdayaan remaja melalui keterampilan vokasional guna menumbuhkembangkan jiwa kewirausahaan di Kabupaten Pinrang - Hendra Jaya; Sapto Haryoko; Saliruddin Saliruddin; Ilham Thaief (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Several related activities include the following: 1)Applying vocational training models in improvingentrepreneurial behaviour for the community (YoungEntrepreneurs, Young Women, and Youth Organization)Paleteang sub-district, Province of Pinrang; 2) Providingguidance to the youth community through mentoring in orderto achieve the desired goals. The companion can also providebenefits as a provision in facing and solving life and lifeproblems as an independent person. Supporting factors forprogram implementation include: (1) sufficient support fromthe district, (2) provision of venue facilities by the district incarrying out activities, (3) good cooperation between localimplementing activities and Youth members. Factorsinhibiting the implementation of activities, among others: (1)limited transportation equipment owned so that it is ratherdifficult to coordinate (2) the distance between the location ofthe activity with the remote head of district office so that it israther difficult to consult with the district (3) lack ofenthusiasm from the community in participating in trainingdue to busyness (work). Based on the achievement of theresults of the courses and training on electronic, computer andmultimedia vocational skills training services Ex. BentengSawitto Village, Paleteang District, Pinrang Regency can besummarized as follows: 1) Increased community participationin electronic service programs, computer maintenance, andgraphic design (multimedia) in Benteng Sawitto Village,Paleteang District, Pinrang Regency; 2) Increasing communityknowledge and skills in electronic service, computermaintenance, and graphic design (multimedia); 3) Increasedpublic awareness about collective behaviour that is not goodfor the economy in Indonesia so that people can repairthemselves if there are damaged.